2005
DOI: 10.1097/00042728-200511000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Severe Complete Pachydermoperiostosis (Touraine-Solente-Golé Syndrome)

Abstract: BACKGROUND. The thickened, folded skin of Touraine-Solente-Golé syndrome (pachydermoperiostosis) can result in cosmetic and fuctional deformities. OBJECTIVE. To illustrate that simple surgical procedures can improve cosmetic and functional status. METHODS. Case report of a 33-year-old male with bilateral eyelid ptosis, enlargement of the eyelids, and a leonine facies owing to deep skin furrows managed with bilateral blepharoplasties and tarsal wedge resections, along with excision of multiple skin furrows. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, there have been several case reports of symptomatic relief with the use of intravenous pamidronate or zolendronic acid [6]. Finally, only for cosmetic purposes, there is the option of performing aesthetic surgery in order to reduce the folds on the face and scalp [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several case reports of symptomatic relief with the use of intravenous pamidronate or zolendronic acid [6]. Finally, only for cosmetic purposes, there is the option of performing aesthetic surgery in order to reduce the folds on the face and scalp [14].…”
Section: Discussionmentioning
confidence: 99%
“…Upon literary review, clinical reports show the use of frontal rhytidectomy, blepharoplasty, facelift, and direct skin excision. [5][6][7][8] We are unaware of any previous use of surgery with concurrent use of botulinum toxin A for the treatment plan of facial pachydermoperiostosis. Our patient underwent primary lateral SMASectomy facelift, secondary glabellar skin and corrugator muscle excision, and concurrent botulinum toxin A to the forehead region.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 The breakdown of the integrity of internal limiting membrane may allow the migration of retinal pigment epithelium and formation of consequent osseous metaplasia. 7 Monselise et al 2 reported that compact bone formation might occur in posttraumatic cases, whereas spongy bone formation was usually associated with intraocular inflammation. Our patient did not have a trauma history; however, the bone formation was in compact type with accompanying bone marrow.…”
mentioning
confidence: 99%
“…As the typical course of this disease is self-limited, with most of the cases ceasing to progress before middle age, the treatment has been mainly focused on cosmetic improvement by plastic surgery. Surgical procedures tried in patients with PDP include procedures such as bilateral blepharoplasties and tarsal wedge resections, along with excision of multiple skin furrows and facelifts (6,7). Frontal rhytidectomy is a relatively new method to improve the deep wrinkles on forehead, which has been tried recently in PDP (8).…”
Section: Discussionmentioning
confidence: 99%